2017
DOI: 10.11648/j.ijhpebs.20170303.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Level of Adherence to Antiretroviral Therapy in People Living with HIV/AIDS at Adama Hospital Medical College Art Clinic, Oromiya Regional State, Ethiopia

Abstract: Both Human Immunodeficiency Virus (HIV) infection and Acquired Immunodeficiency Syndrome (AIDS) remain major public health problems in Ethiopia. Good adherence to antiretroviral therapy is necessary to achieve the best virological response, lower the risk of treatment failure and drug resistance, and reduce morbidity and mortality. There are many alterable factors known to affect the treatment adherence. In this regard, there have been very limited researches particularly in Adama. Therefore, this study was ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The abstracts and full text of the remaining 25 studies were assessed and screened for eligibility criteria and whether they reported the outcome variable of interest (adherence); 18 articles were excluded due to failure to meet inclusion criteria. Two articles were excluded due to poor quality based on the selection criteria [17, 26]. Four articles were excluded because their regression tables did not include disclosure as an independent variable [27–30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abstracts and full text of the remaining 25 studies were assessed and screened for eligibility criteria and whether they reported the outcome variable of interest (adherence); 18 articles were excluded due to failure to meet inclusion criteria. Two articles were excluded due to poor quality based on the selection criteria [17, 26]. Four articles were excluded because their regression tables did not include disclosure as an independent variable [27–30].…”
Section: Resultsmentioning
confidence: 99%
“…While the relationship between disclosure and adherence is fairly well-established in high-income settings, fewer studies have investigated the association in sub-Saharan Africa. Studies that have examined the association between ART adherence and disclosure among PLWHA in Ethiopia in particular have presented inconsistent results, with some finding strong positive associations and others finding limited or even negative associations between the two factors [17, 18]. The one existing systematic review of factors related to adherence in sub-Saharan Africa included only a handful of articles that examined the effect of disclosure specifically [6].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the articles' adherent status to HAART was measured using self-report and taking ≥95% of the prescribed doses of medication is considered as good adherence to HAART (Table 1). Adherence to HAART Among 15 cross-sectional studies, the prevalence of adherence to HAART ranged from 65% (27,29) to 92.6% (25). The overall pooled prevalence of adherence to HAART is found to be 81.2% (80.1-82.3)( (Fig 2).…”
Section: Characteristics Of the Articlesmentioning
confidence: 96%
“…To determine the effects of serostatus disclosure on adherence to HAART among PLWHIV in Ethiopia, a total of four cross-sectional studies (23)(24)(25)(26) were used. This study revealed that clients who disclosed their serostatus to someone else are nearly three times more likely to adhere to their HAART compared to clients who did not disclose their serostatus(AOR= 2.99, 95%CI: 1.88, 4.77) (Fig 4).…”
Section: The Effects Of Serostatus Disclosure On Adherence To Haartmentioning
confidence: 99%
“…Evidence from a systematic review of adherence to ART in SSA also indicated that the average ART adherence score was 72.9% (5). In Ethiopia adherence to ART ranged from 63.8%-95.5% (6)(7)(8)(9)(10), most of them were below the WHO recommendation.…”
Section: Introductionmentioning
confidence: 99%